School-based intervention impacts availability of vegetables and beverages in participants’ homes - Hudson, Erin A.; Burgermaster, Marissa; Isis, Sophia M.; Jeans, Matthew R.; Vandyousefi, Sarvenaz; Landry, Matthew J.; Seguin-Fowler, Rebecca; Chandra, Joya; Davis, Jaimie (Frontiers in Nutrition, 2023)
As rates of metabolic syndrome rise, children consume too few vegetables and too much added sugar. Because children tend to eat what is available at home, the home environment plays a key role in shaping dietary habits. This secondary analysis evaluated the effects of a school-based gardening, cooking, and nutrition education intervention (TX Sprouts) compared to control on the availability of vegetables, fruit juice, and sugarsweetened beverages (SSBs) at home. In the TX Sprouts cluster-randomized trial, 16 schools were randomized to TX Sprouts (n=8 schools) or control (n=8 schools) for one academic year. All schools served predominately Hispanic families with low incomes. TX Sprouts built school gardens and taught 18 lessons to all 3 rd -5 th grade students at intervention schools. TX Sprouts also offered monthly caregiver lessons before and/or after school. Caregivers completed questionnaires pre and post, providing demographics and information about home availability of vegetables, fruit juice, and SSBs. Summary statistics were used to describe the sociodemographic characteristics of participants.Linear regression assessed the change in scores (pre to post) for the food/ beverage availability question. The model was adjusted for the caregiver's education, employment status, child's grade, and free or reduced-price lunch eligibility. The analytic sample included 895 participants. Compared to control, the intervention positively changed the home availability of targeted foods and beverages, largely by improving the availability of vegetables and vegetable juice. This study showed that a school gardening, nutrition, and cooking program delivered to elementary children may positively influence the home food environment.